Simulated data set for SAXS tensor tomography, sample "M" - Nielsen, Leonard; Erhart, Paul; Liebi, Marianne (Chalmers University of Technology, 2022)
This is a simulated data set intended for testing SAXS tensor tomographic reconstructions, including the original field from which the data was generated.
Keywords: Physical Sciences; Fysik